Long-Term Hypoparathyroidism and Hypophosphatemia in Dialysis Patients - Linda Shavit MD; Meyer Lifschitz MD; Itzchak Slotki MD (SAGE Publishing, 2014)
Background and Objectives . Hypoparathyroidism in patients with functioning kidneys leads to hyperphosphatemia. This article reviews data suggesting that hypoparathyroidism in patients on dialysis leads to hypophosphatemia. Design . Clinical data of the following were reviewed: ( a ) a patient with hypoparathyroidism before and during chronic dialysis; ( b ) patients on dialysis with surgically created hypoparathyroidism; ( c ) dialysis patients being treated with Cinacalcet, a calcium-sensing receptor agonist that lowers parathyroid hormone (PTH) levels; and ( d ) dialysis patients being treated with Velcalcetide, a new calcium-sensing receptor agonist that also lowers PTH. Results . In the patient presented in this study, in patients with surgically created hypoparathyroidism, and those receiving Cinacalcet or Velcalcetide, a fall in PTH was associated with hypophosphatemia or a fall in serum phosphorus. Conclusion . In patients on dialysis, hypoparathyroidism may lead to hypophosphatemia.